Pengaruh Budaya Organisasi Dan Kepuasan Kerja Terhadap Turnover Intentions Karyawan Pada PT.Niagamas Gemilang Di Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - Nilam Anggar Sari; Rina Angelina; Idham Idham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The object of this research was carried out at PT. Niagamas Gemilang is a growing Foreign Investment Company in the field of Oil Palm Plantation with the Manager Mr. Haribuang Senobroto having the address at Sungai Payang Village, Loa Kulu District, Kutai Kartanegara Regency, 17 Rt.10 with a total number of 1,405 employees. The purpose of this study is to Know, Are Organizational Culture Variables and Job Satisfaction Influence Simultaneously Against Turnover Intentions of Employee Employees at PT. Niagamas Gemilang In Loa Kulu Subdistrict, Kutai Kartanegara Regency, To Know, Are Organizational Culture Variables And Job Satisfaction Partially Influence On Turnover Intentions Of Employees At PT. Niagamas Gemilang in Loa Kulu Subdistrict, Kutai Kartanegara Regency and To Know, From the two variables, which variable has the most dominant influence on Turnover Intentions of Employees at PT. Niagamas Gemilang in Loa Kulu District, Kutai Kartanegara Regency.A population of 132 people and a sample of 66 employees.The first hypothesis which states "That, Organizational Culture Variables and Job Satisfaction Influence Simultaneously Against the Desire to Switch Employees at PT. Niagamas Gemilang in Loa Kulu Subdistrict, Kutai Kartanegara Regency "was accepted and proven true. The second hypothesis states that, Organizational Culture Variables Influentially Influence the Desire to Change Employees at PT. Niagamas Gemilang in Loa Kulu Subdistrict, Kutai Kartanegara Regency was accepted and proved to be true. The second hypothesis states "That, Variable Job Satisfaction Partially Influences the Desire to Change Employees at PT. Niagamas Gemilang in Loa Kulu Subdistrict, Kutai Kartanegara Regency "was accepted and proven true. The third hypothesis in this study "That, Organizational Culture variables have the most dominant influence on the desire to move employees at PT. Niagamas Gemilang in Loa Kulu Subdistrict, Kutai Kartanegara Regency "was accepted and proven true. Keywords: Organizational Culture, Job Satisfaction, Turnover Intentions